2013
DOI: 10.1093/cercor/bht154
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reappraisal of Emotion: A Meta-Analysis of Human Neuroimaging Studies

Abstract: In recent years, an explosion of neuroimaging studies has examined cognitive reappraisal, an emotion regulation strategy that involves changing the way one thinks about a stimulus in order to change its affective impact. Existing models broadly agree that reappraisal recruits frontal and parietal control regions to modulate emotional responding in the amygdala, but they offer competing visions of how this is accomplished. One view holds that control regions engage ventromedial prefrontal cortex (vmPFC), an are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

167
1,429
11
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,501 publications
(1,668 citation statements)
references
References 117 publications
167
1,429
11
8
Order By: Relevance
“…Precentral and postcentral gyri are involved in somatosensory processing and voluntary movement and have also been shown to activate during emotion regulation (Buhle et al, 2014;Goldin et al, 2008;Kohn et al, 2014). Though these regions have previously been related to treatment response in anxious adults (Klumpp et al, 2013;Phan et al, 2013), very …”
Section: Discussionmentioning
confidence: 99%
“…Precentral and postcentral gyri are involved in somatosensory processing and voluntary movement and have also been shown to activate during emotion regulation (Buhle et al, 2014;Goldin et al, 2008;Kohn et al, 2014). Though these regions have previously been related to treatment response in anxious adults (Klumpp et al, 2013;Phan et al, 2013), very …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it may be possible to harness the type of emotional perspective-taking studied here as an emotion regulation strategy, aimed at helping individuals cope with emotional distress. Extant research within the field of emotion regulation has shown that people can effectively down-regulate negative affect by using topdown cognitive control (2). However, a limitation of many cognitive emotion regulation strategies is that they depend on attentional, linguistic, and working memory systems supported by lateral prefrontal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, it isn't surprising that the last decade has seen enormous growth in behavioral and brain research asking how we can effectively regulate our emotions. Although this work has made many important advances (1,2), it has focused almost entirely on cognitive regulatory strategies that involve controlling attention to and/or rethinking the meaning of stimuli and events. As such, this work has completely overlooked the way in which social cognitive processes can be used to regulate our emotions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, dlPFC and also mPFC activity were related to cognitive reappraisal and mindfulness as strategies to regulate one's emotions (Opialla et al., 2015). Furthermore, prior research has shown that the dlPFC indirectly modulates amygdala activity through connections with the vmPFC (Buhle et al., 2014). Engaging the dlPFC might be particularly important to exert cognitive control in terms of cognitive reappraisal of negative emotional self‐content throughout the practice of the daily Perspective Dyad (Böckler, Herrmann, et al., 2017; Holmes et al., 2007).…”
Section: Discussionmentioning
confidence: 99%